Translation and validation of the Malay version of the Stroke Knowledge Test - Sowtali, Siti Noorkhairina; Mohd Yusoff, Dariah; Harith, Sakinah; Mohamed, Monniaty (Elsevier, 2016)
Background: To date, there is a lack of published studies on assessment tools to evaluate the effectiveness of stroke education programs. Methods: This study developed and validated the Malay language version of the Stroke Knowledge Test research instrument. This study involved translation, validity, and reliability phases. The instrument underwent backward and forward translation of the English version into the Malay language. Nine experts reviewed the content for consistency, clarity, difficulty, and suitability for inclusion. Perceived usefulness and utilization were obtained from experts’ opinions. Later, face validity assessment was conducted with 10 stroke patients to determine appropriateness of sentences and grammar used. A pilot study was conducted with 41 stroke patients to determine the item analysis and reliability of the translated instrument using the Kuder Richardson 20 or Cronbach’s alpha. Results: The final Malay version Stroke Knowledge Test included 20 items with good content coverage, acceptable item properties, and positive expert review ratings. Psychometric investigations suggest that Malay version Stroke Knowledge Test had moderate reliability with Kuder Richardson 20 or Cronbach’s alpha of 0.58. Improvement is required for Stroke Knowledge Test items with unacceptable difficulty indices. Overall, the average rating of perceived usefulness and perceived utility of the instruments were both 72.7%, suggesting that reviewers were likely to use the instruments in their facilities. Conclusions: Malay version Stroke Knowledge Test was a valid and reliable tool to assess educational needs and to evaluate stroke knowledge among participants of group-based stroke education programs in Malaysia